General theoretical characteristics of money obligations arising under hiring (lease) contracts - Mudryi, Oleksandr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article analyzes the concept of monetary obligations and their place in contractual obligations of hiring (lease). The term "monetary obligation" aims to understand this concept as specific in relation to the more general concept – "obligation". It can be assumed that this was the main reason that the majority of definitions of monetary obligation presented in science and judicial practice contain the concept of "legal relationship" (or "obligation").The author justifies the position that the term "monetary obligation" should be considered from two points of view:1) as an obligation (a type of civil legal relationship) in which the debtor is obliged to pay money in favor of the creditor, and the creditor has the right to demand that the debtor fulfill this obligation. This understanding of a monetary obligation refers to simple obligations, the content of which is exhausted by the obligation of the debtor to pay money and the right of the creditor to demand such payment (for example, a monetary obligation that arises on the basis of an interest-free money loan contract);2) as a structural element of the content of a complex obligation, in which the obligation of the debtor to pay money and the corresponding right of the creditor to demand such payment exist alongside other rights and obligations of the parties to the same obligation.The contract of hiring (lease) is the ground for the appearance of a complex civil legal obligation as a legal relationship within the meaning of Part 1 of Art. 509 of the Civil Code of Ukraine. Accordingly, it is advisable to consider the monetary obligation as a structural element of the above-mentioned complex obligation. The monetary obligation under the contract of employment (lease) consists, first of all, in the obligation of the lessee to pay a charge for the use of the property (rent), if in accordance with the terms of the contract and the requirements of the law, the latter is paid in money, and it may also be in other obligations of the parties to pay money (reimbursement of the cost of capital repairs, reimbursement of expenses related to the improvement of leased property, etc.). Monetary obligations under employment contracts (lease) have a civil law nature, regardless of the subject structure of the parties to the relevant contract.